2014
DOI: 10.3390/molecules19056489
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Resin Composition in the Andean Tree Austrocedrus chilensis

Abstract: Abstract:Little is known about the changes in resin composition in South American gymnosperms associated with the different seasons of the year. The diterpene composition of 44 resin samples from seven Austrocedrus chilensis (Cupressaceae) trees, including male and female individuals, was investigated in three different seasons of the year (February, June and November). Twelve main diterpenes were isolated by chromatographic means and identified by gas chromatography-mass spectrometry and nuclear magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Thus, the current variation in the results can also be attributed to the tree’s genetic diversity and climatic conditions. This is also in correlation with the results published [ 74 76 ] where it was shown that both genetic and climatic factors can influence the resin production and composition. To further confirm expression of amyrin related transcripts, primers were designed using known available genomic sets derived from Azadirachta indica .…”
Section: Resultssupporting
confidence: 92%
“…Thus, the current variation in the results can also be attributed to the tree’s genetic diversity and climatic conditions. This is also in correlation with the results published [ 74 76 ] where it was shown that both genetic and climatic factors can influence the resin production and composition. To further confirm expression of amyrin related transcripts, primers were designed using known available genomic sets derived from Azadirachta indica .…”
Section: Resultssupporting
confidence: 92%
“…Several minor compounds also occurs in the fraction, including the isomers E -communic acid 7 and Z -communic acid 8 as well as the minor components 1 , 5 , and 9 , identified by comparison with literature [18]. GC-MS analysis showed a main compound at Rt = 16.16 min., identified as torulosal 6 , E -communic acid methyl ester 7a (Rt = 15.97 min, m / z = 316); Z -communic acid methyl ester 8a (Rt = 15.71 min, m / z = 316) and 12-oxolabda-8(17), 13 E -dien-19 oic acid methyl ester 9a (Rt = 17.89 min, m / z = 332), all of them in agreement with the literature [18,19].…”
Section: Resultssupporting
confidence: 89%
“…The resin profiles from healthy trees were similar to those described by Olate et al . (2014) [19] for female and male individuals from a Chilean population of A. chilensis . However, naturally and artificially infected trees showed a distinctive and different profile with relevant changes in chemical composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar case was observed in Canarium strictum in Kolli Hills and Servarayan Hills where the informants reported that male trees produce less resin than the female trees, and when inquired further about the quality variation between the two gender the informants did not comment on any quality variation in male and female plant resins, but informed about a general variation that based on the dryness of the resin that the fragrance it produces varies. For example, resin composition of male and female trees of Austrocedrus chilensis (D. Don) Florin & Boutelje (Cupressaceae) is reported to vary between genders and during different seasons of the year (Olate et al, 2014).…”
Section: Gender Preference In Food and Medicinal Usagesmentioning
confidence: 99%